2011
DOI: 10.1673/031.011.17601
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Vectors Survey in the AL-Ahsaa District of Eastern Saudi Arabia

Abstract: The present study aimed to identify the mosquito vectors distributed throughout AL-Ahsaa district situated in the eastern region of Saudi Arabia. Mosquito larvae were collected seasonally for one year (October 2009 to September 2010) from different breeding sites in seven rural areas utilizing long aquatic nets. Salinity and pH of these breeding sites were also measured seasonally. The survey revealed the presence of five mosquito species, Aedes caspius Pallas (Diptera: Culicidae), Anopheles multicolor Camboul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…All the mosquito species that have been collected in the present study never been mentioned in the survey of Büttiker [17]. Additionally, the recent survey by Ahmed et al [19] did not report the presence of both Cs. longiareolata and Cs.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…All the mosquito species that have been collected in the present study never been mentioned in the survey of Büttiker [17]. Additionally, the recent survey by Ahmed et al [19] did not report the presence of both Cs. longiareolata and Cs.…”
Section: Discussionmentioning
confidence: 67%
“…Results also showed that this mosquito is a cool weather speciesas the highest incidence was in winter and spring. Similarly, Ahmed et al [19] stated that winter season exhibited the highest incidence of larvae compared with the other three seasons in Al-Ahsa district, Eastern Saudi Arabia. In contrast, Abdullah and Merdan [28] mentioned that Cx.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations